Analysis of Consumer Perceptions of Food Safety Risk Aspects in the Food Supply Chain System - Hana Catur Wahyuni; Wiwik Sumarmi; Ida Agustini Saidi (Universitas Muhammadiyah Sidoarjo, 2018)
Food security has an important role in human health. Food that is not guarded can be contaminated which has a negative impact on human health. The negative impact arose due to contamination originating from various places, starting from raw materials, processes, distribution etc. In other words, contamination can be sourced from all actors chained to the supply. For this reason, consumers must be able to choose foods that are safe for consumption. This study aims to determine the extent of consumer perceptions of aspects of food safety risk. The study was conducted by distributing questionnaires and processed using one way statistics. The results of the study show that food safety is the main element that is considered in carrying out the food purchasing process.